(untitled) (Economics and region, 2022)
Introduction. Today’s new challenges dictate changes to the basic approaches to the formation of strategic vectors for strengthening the energy security of the state. Risk-oriented problems are extremely important factors producing such changes. In addition, they are strengthened by the consequences of russia’s invasion of the territory of Ukraine. It is clear that the previously stated basic approaches to the formation of strategic vectors for strengthening the energy security of the state have changed and transformed into new approaches. Taking into account the changing environment of today, the energy security of the state, which needs support from international institutions, and the identification of an exo-unification approach to the formation of strategic vectors for its strengthening, is gaining special relevance. Purpose. To study the energy security of the state through the prism of domestic and global scale, which will make it possible to determine the basic approaches to the formation of strategic vectors for its strengthening. Method (methodology). In the research process, such methods as logical were used, which made it possible to analyze scientific works in the field of energy security of the state; analysis and synthesis that made it possible to single out the basic approaches to the formation of strategic vectors for its strengthening. Results. The essential characteristics of the state’s energy security are characterized. Attention is focused on its understanding through the regulatory and legal basis. Nineteen basic approaches to the formation of strategic vectors for strengthening the energy security of the state are singled out, among which eight of them are in constant interaction (resource-technological, departmental, ecological, social, managerial, descriptive, geopolitical and economic). A detailed analysis of the basic approaches determined an exo-unifying approach, which will allow the implementation of an optimistic development scenario through the prism of constant interaction between all approaches with consumer-centric elements. It was established that the basic approaches interact with each other, complement each other and create a synergy effect.